The American consumer: Reforming, or just resting? - Christopher D. Carroll; Jirka Slacalek (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
American households have received a triple dose of bad news since the beginning of the current recession: The greatest collapse in asset values since the Great Depression, a sharp tightening in credit availability, and a large increase in unemployment risk. We present measures of the size of these shocks and discuss what a benchmark theory says about their immediate and ultimate consequences. We then provide a forecast based on a simple empirical model that captures the effects of wealth shocks and unemployment fears. Our short-term forecast calls for somewhat weaker spending, and somewhat higher saving rates, than the Consensus survey of macroeconomic forecasters. Over the longer term, our best guess is that the personal saving rate will eventually approach the levels that preceded period of financial liberalization that began in the late 1970s.
urn:nbn:de:hebis:30-68317
Keywords: C61; D11; E24; 330; Consumption/Saving Forecast; Credit Crunch; Financial Crisis; Privater Haushalt; Konsumentenverhalten; Sparen; Schock; Finanzmarktkrise; Vermögenseffekt; Arbeitslosigkeit; USA